Malignant tracheal tumors. Issue 4 (July 2015) - Sherani, Khalid; Vakil, Abhay; Dodhia, Chetan; Fein, Alan
<x xml:space="preserve">Abstract</x> Purpose of review This article reviews the current literature for the purpose of developing a practical approach for the diagnosis and management of primary tracheal tumors. Recent findings Because of nonspecific symptoms, tracheal tumors remain a diagnostic challenge. Currently available management strategies are not being optimally utilized due to lack of physician awareness and knowledge. The use of newer diagnostic modalities has increased diagnostic accuracy resulting in earlier detection in recent years. This review describes currently available diagnostic modalities along with relatively newer ones such as virtual bronchoscopy, anatomic Optical Coherence Tomography, spectroscopic techniques, and endobronchial ultrasonography. We will review and discuss management strategies including surgical options, adjuvant therapies, and interventional pulmonary techniques including their role in palliation. Summary Early detection along with improved surgical and interventional pulmonology techniques has led to a decline in the death rates from tracheal cancer in recent years. However, further studies are required to define the role of chemotherapeutic agents, combination therapies, and novel techniques such as tracheal transplantation, in the management of primary tracheal tumors. More robust evidence-based studies are needed to provide evidence for clinical practice guidelines for the treatment of primary tracheal tumors.